Strengthening Marketing Innovation In MSMEs Business Incubators In Kraftangan Malaysia Selangor Branch - Audita Nuvriasari; Norlaile Binti Salleh Hudin; Hasim As’ari; Noraine binti Salleh Hudin (International Journal Of Community Service, 2023)
The International community service partners are MSMEs business incubators under the auspices of Kraftangan Malaysia Selangor Branch. The purpose of community service activities is to increase partners' awareness of the importance of innovation, one of which is marketing innovation in order to develop and improve the business performance of MSMEs. The activity method is to provide education to partners through counseling programs. The result of community service is an increase in partners' knowledge about marketing innovation in the form of product innovation and packaging to be able to develop in their business.